Nagô Grandma and White Papa : Candomblé and the creation of Afro-Brazilian identity - Dantas, Beatriz Góis (Latin America in translation/en traducción/em tradução., 2009)
In this signal work in Brazilian anthropology and African diaspora studies, Dantas compares the formation of religious traditions and ethnic identities in the Brazilian states of Sergipe and Bahia, revealing how they diverged from each other due to their different social and political contexts and needs. This volume makes the book, originally published in Brazil, available in English for the first time.